The impact of transparency constraints on the efficiency of the Russian healthcare system: systematic literature review. (31st December 2023) - Timofeyev, Yuriy; Dremova, Oksana; Jakovljevic, Mihajlo
Abstract: There is an ongoing debate among researchers and policy-makers on how to make transparency a powerful tool of healthcare systems. This study addresses how the availability and accessibility of information about medical services to the general population affects healthcare outcomes in Russia. A systematic review was conducted and reported according to the Preferred Reporting Items for Systematic Reviewing and Meta-Analysis (PRISMA) guidelines. Transparency indicators of health facilities used in the world's most efficient healthcare systems are also reviewed. Although the increase of transparency in the Russian healthcare system is considered as a tool for improving its efficiency, very little has been done to improve the actual level of transparency. The existing institutional specifics of the Russian healthcare system impose serious restrictions on acceptable levels of transparency. In the reviewed empirical Russian studies, transparency is often viewed simplistically as either information available on the websites of medical organizations or issues related to the amount of accessible indicators of compulsory medical statistical reporting. The novelty of this study consists in (a) reviewing the most recent studies on the topic and (b) including studies in Russian in the analysis. We elaborate on general and specific policy implications for improving transparency-driven outcomes in the Russian healthcare system.